2009
DOI: 10.1158/0008-5472.can-09-1101
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Chemotherapeutic Agents Based on Their DifferentialIn vitroEffects on Dendritic Cells

Abstract: Despite the crucial roles dendritic cells (DC) play in host immunity against cancer, the pharmacologic effects of many chemotherapeutic agents have remained mostly unknown. We recently developed a DC biosensor clone by engineering the stable murine DC line XS106 to express the yellow fluorescent protein (YFP) gene under the control of interleukin (IL)-1B promoter. In this study, the resulting XS106 pIL1-YFP DC clone was used to screen 54 anticancer drugs. Each drug was tested at five concentrations (0.1-10 Mmo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 32 publications
2
105
0
Order By: Relevance
“…An unbiased functional screen of 54 chemotherapeutic agents unveiled striking diversity of the tested drugs on the maturation, survival and growth of DCs. 24 The drugs delivering DC maturation signals at concentrations causing only marginal DC death included topoisomerase inhibitors (for example, etoposide, mitoxantrone, doxorubicin), antimicrotubule agents (for example, vinblastine, paclitaxel, docetaxel) and the two alkylating agents mechlorethamine and diaziquone. 24 In another report, paclitaxel, doxorubicin and methotrexate were shown to promote the ability of murine BM-DCs to present antigens to T-cells in vitro by upregulating antigen-processing machinery gene components, costimulatory molecules and IL-12p70.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…An unbiased functional screen of 54 chemotherapeutic agents unveiled striking diversity of the tested drugs on the maturation, survival and growth of DCs. 24 The drugs delivering DC maturation signals at concentrations causing only marginal DC death included topoisomerase inhibitors (for example, etoposide, mitoxantrone, doxorubicin), antimicrotubule agents (for example, vinblastine, paclitaxel, docetaxel) and the two alkylating agents mechlorethamine and diaziquone. 24 In another report, paclitaxel, doxorubicin and methotrexate were shown to promote the ability of murine BM-DCs to present antigens to T-cells in vitro by upregulating antigen-processing machinery gene components, costimulatory molecules and IL-12p70.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…For the dolastatin 10/vaccination treatment combination, a single dose of dolastatin 10 (0.4 mg/kg) was administered intravenously 15 …”
Section: Analysis Of DC Homing To Tumor-draining Lnsmentioning
confidence: 99%
“…Nevertheless, only a few studies have been reported that have investigated the capacity of antitumor therapeutics to improve DC function. Recent work has identified several cytotoxic agents, including the mitotic spindle inhibitor vinblastine, as potent activators of DC maturation (14)(15)(16). Although the underlying mechanism is still poorly defined, these data clearly highlight a previously unrecognized immunostimulatory activity for vinblastine.…”
Section: Introductionmentioning
confidence: 99%
“…14 The kinetic experiments showed that there was a time lag between the appearance of the Sytox þ cells (at 6 h) and neutrophil influx (at 16-38 h All these data suggest that the recruitment of neutrophils is associated with apoptotic cells that are killed in situ by doxorubicin. Of note, it has been recently shown that doxorubicin does not have a direct immunostimulatory activity on antigen-presenting cells, 32 thereby excluding a direct effect of doxorubicin on the host cells. Only some apoptotic stimuli, including anthracyclines, induce an immunogenic form of apoptosis characterized by surface exposure of CRT and release of HMGB1.…”
Section: N=10 N=12 N=9mentioning
confidence: 99%